661 PROGNOSTIC FACTORS OF DEPRESSION AFTER HIP FRACTURE SURGERY: SYSTEMATIC REVIEW. (8th March 2022) - Milton-Cole, R; Ayis, S; Lambe, K; O'Connell, M D L; Sackley, C; Sheehan, K J
Abstract: Introduction: Patients with hip fracture and depression are less likely to recover. This review aimed to identify prognostic factors of depression up to one year after hip fracture surgery in adults. Secondary aims were to determine whether identified factors are modifiable or non-modifiable and describe proposed underlying mechanisms for their association with depression. Methods: We searched MEDLINE, Embase, PsychInfo, CINAHL and Web of Science Core Collection databases for published studies as well as grey literature. We did not impose any date, geographical, or language limitations. Two reviewers independently screened studies against predefined eligibility criteria to identify relevant papers. We included observational studies investigating prognostic factors of depression up to one year after surgery in adults surgically managed for non-pathological hip fracture. Two reviewers independently extracted data (Checklist for critical Appraisal and data extraction for systematic Reviews of prediction Modelling Studies, adapted for use with prognostic factors studies Checklist) and completed quality appraisal (using Quality in Prognosis Studies tool). Results: 3, 402 studies were identified; 2, 915 studies were excluded leaving 13 studies included in this review. 3, 769 patients were included across all studies with a mean age ranging from 76.21–81.82 years. A total of 39 prognostic factors were investigated and most studies failed to identify a primary prognostic factor of interest. Most of these factors were patient factors with only a few being process or structure factors. Conclusion: Various potential prognostic factors of depression after hip fracture were identified however, Methodological quality and heterogeneity between studies limited the certainty of which prognostic factors were the strongest. High-quality research investigating prognostic factors using the same study design, Methodology and measurements is warranted to allow for comparisons of the predictive power of factors. As well as future research into the underlying mechanisms of prognostic factors.